Assessing sexual dysfunction in patients with external genital endometriosis - E. Begovich; A. G. Solopova; S. V. Khlopkova; E. A. Son; J. Yu. Ungiadze; L. E. Idrisova (Акушерство, гинекология и репродукция, 2022)
Introduction. External genital endometriosis (EGE) is a chronic, relapsing disease that affects various aspects of sexual function, the quality of sexual and interpersonal relationships, physical and psycho-emotional health and leads to social maladjustment and anxiety-depressive disorders, resulting in progressively decreased quality of life (QoL).Aim: to analyze an impact of sexual disorders on QoL of women with painful and painless EGEs.Materials and Methods. A prospective comparative randomized interventional study involved 160 patients (110 and 50 women with painful and painless EGE, respectively) of reproductive age, with laparoscopically and morphologically verified diagnosis according to the revised American Fertility Society scoring system (R-AFS, 1996). Pain syndrome and sexual dysfunction were assessed using specialized questionnaires: visual analogue scale (VAS), PainDETECT, and Female Sexual Function Index (FSFI). After surgical treatment, 8 patients refused to participate in the study (6 with painful EGE and 2 with painless EGE). Thus, only 152 women passed all stages of the study. The patients were divided into 4 groups depending on the presence and/or absence of pain syndrome and the tactics of the rehabilitation period ("active" or "passive"): group IA consisted of 49 (47.1 %) women with pain and "active" rehabilitation; group IБ – 55 (52.9 %) women with pain syndrome and "passive" rehabilitation tactics; group IIA – 23 (47.9 %) patients without pain syndrome with "active" rehabilitation; group IIБ – 25 (52.1 %) patients without pain syndrome with "passive" rehabilitation tactics.Results. Women with painful vs. painless EGE were found to have a more severe course of the disease and a markedly decreased quality of sexual life. It was observed that patients with "active" rehabilitation tactics (groups IA and IIA) had intensity of the pain syndrome and the neuropathic pain component significantly decreased, improved parameters of the quality of sexual life, sexual desire and sexual excitability compared to patients with "passive" rehabilitation tactics applied with the measures within the framework of the National Clinical Guidelines (groups IБ and IIБ).Conclusion. A significantly decreased quality of sexual life of EGE patients indicates a need for assessing and correcting sexual disorders as well as introducing early onset of rehabilitation measures by using a multidisciplinary approach.